Analysis of Factors Affecting Muzakki Motivation in Paying Professional Zakat (Case Study on State Civil Servant in Cilacap Regency) - Ubaidillah; Akhris Fuadatis Solikha (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2023)
This study aims to analyze the factors that influence the motivation of muzakki in paying professional zakat on the State Civil Servant of Cilacap Regency. The factors studied were religiosity, government regulations, service quality, institutional trust, income, knowledge of zakat, level of zakat promotion, accountability, and transparency. This study uses a quantitative approach with multiple linear regression analysis. The population in this study are State Civil Sevant in Cilacap who are Muslim and have distributed professional zakat. The sampling method used in this study is accidental sampling method. In this study, a questionnaire was used, both filled offline and online using Google Form with a total of 223 respondents. The results of this study indicate that the variables of religiosity, knowledge, and transparency have a significant positive effect on the motivation of muzakki of the State Civil Servant in Cilacap Regency in paying professional zakat. Government regulation variables, service quality, income level, promotion level, accountability have no significant effect on the motivation of the Cilacap Regency State Civil Servant muzakki in paying professional zakat. Meanwhile, the institutional trust variable has a significant negative effect on the motivation of the State Civil Servant of Cilacap Regency in paying professional zakat.